In-between spaces for today's city: Historical review for identifying their beneficial characteristics - Aimar Santos-Garcia; Izaskun Aseguinolaza Braga (Frontiers of Architectural Research)
Experts question why cities, which are supposedly built for citizens, fail to address their social needs. Everyday life is challenging in our cities, especially because public spaces have generally been arranged and designed by considering the physical environment and without consideration for how these spaces should facilitate human interactions. This paper identifies “in-between spaces” as key scenarios for addressing this issue. These spaces offer the opportunity to feel comfortable and safe, foster a sense of community, and facilitate connections.Little has been written about these spaces and, particularly, their characteristics. Therefore, the objective of this study is to provide a more in-depth understanding of in-between spaces by examining literature on such spaces throughout city history.The results underscore the threshold character as the primary feature of in-between spaces and define various types of in-between spaces depending on their position within the gradient between public and private domains. The analysis also identified recurring characteristics, such as presence of reproductive labor, vegetation, or amenities, tendency to be programmed or unprogrammed within interior or exterior spaces and establishes relationships between these characteristics. Furthermore, the results suggest that the values promoted by these spaces and their recurring features can offer solutions to regenerate cities.